1990
DOI: 10.1128/iai.58.3.703-710.1990
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an immunostimulating protein from Mycobacterium leprae

Abstract: Despite the recent identification of a number of Mycobacterium leprae proteins, the major immunogenic determinants of this organism remain obscure. We isolated from M. leprae a potent immunostimulatory preparation, designated the MLP fraction, which contains a major protein of 35 kilodaltons (kDa). This protein was precipitated by monoclonal antibody ML03-A,, which recognizes a 35-kDa protein of M. leprae, and by sera obtained from patients with lepromatous leprosy. Neither sera from healthy controls nor sera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Our approach has been to isolate the M. leprae components and assess their abilities to be recognized by lymphocytes of responsive patients with leprosy and confer protection against infection with leprosy bacilli in mice. Using a number of extraction procedures, we have isolated strong T-cell immunogens from M. leprae (20,21). In the present study, we demonstrated that immunization with cell wall-associated proteins of M. leprae (CWIF, (Fig.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Our approach has been to isolate the M. leprae components and assess their abilities to be recognized by lymphocytes of responsive patients with leprosy and confer protection against infection with leprosy bacilli in mice. Using a number of extraction procedures, we have isolated strong T-cell immunogens from M. leprae (20,21). In the present study, we demonstrated that immunization with cell wall-associated proteins of M. leprae (CWIF, (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…An analysis of the precursor frequency of antigen-reactive human peripheral T cells suggests that as many were sensitive to the M. leprae cell wall protein peptidoglycan complex as to M. leprae itself (20). Independently, Mohagheghpour et al (21) have partially purified a 35-kilodalton protein from the pelleted fraction of sonicated M. leprae. This preparation, the M. leprae protein fraction designated MLP, not only reacts with circulating antibodies from patients with leprosy but, more importantly, elicits in vitro T-lymphocyte responses from patients with leprosy that parallel their responses to whole M. leprae cells.…”
mentioning
confidence: 99%
“…Though T lymphocytes play a major role in protection against facultative intracellular bacteria, antigens relevant to the humoral immune response have been studied more extensively than T-cell antigens because antigens recognized by antibodies are more technically amenable to study (40). To identify antigens recognized by T lymphocytes, complex protein preparations from intracellular bacteria have been used to investigate the cellular immune response (12,18,37). However, isolation of individual stimulatory components in complex mixtures is still difficult.…”
mentioning
confidence: 99%
“…Most leprosy patients and contacts, but not TB patients, showed T cell proliferation or IgG response to the 35kDa protein of M. leprae 52,53 demonstrating its specificity. In both ELISA and dipstick assays, a relatively high sensitivity was obtained for both MB (70-100%) and PB (40-60%) of leprosy patients.…”
Section: Accepted M Manuscriptmentioning
confidence: 92%